2014
DOI: 10.1002/maco.201307588
|View full text |Cite
|
Sign up to set email alerts
|

Microstructure and bio‐corrosion behavior of Mg–Zn and Mg–Zn–Ca alloys for biomedical applications

Abstract: The microstructure and bio-corrosion behavior of binary Mg-xZn (x ¼ 1.25, 2.5, 4) and ternary Mg-Ca-xZn (x ¼ 1.25, 2.5, 4) alloys have been studied using scanning electron microscopy (SEM), electrochemical, and immersion tests. Microstructure analysis indicated that the binary Mg-Zn alloys are composed of primary a-Mg matrix and Mg 12 Zn 13 phases, while, ternary Mg-Ca-Zn alloys are composed of a-Mg, Mg 2 Ca, and IM1 (Ca 3 Mg x Zn 15Àx ) (4.6 x 12) phases or a-Mg, IM1 and IM3 (Ca 2 Mg 5 Zn 13 ) phases. Electro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
36
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 111 publications
(43 citation statements)
references
References 27 publications
3
36
0
1
Order By: Relevance
“…The consideration of the two ternary compounds reported by Clark-Ca2Mg6Zn3 and Ca2Mg5Zn13-resulted in the best consistency with the experimental results reported in the literature, e.g., [33]. Bakhsheshi-Rad et al [38] investigated the influence of Zn content on the microstructure, phase compositions and corrosion resistance of binary Mg-xZn and ternary Mg-0.8Ca-xZn (x = 1.25, 2.5, 4 wt %) alloys. The effect of the Ca content in Mg-4Zn-xCa (x = 0.18-2.2 wt %) on the microstructure, phase composition and morphology has been systematically studied by Zhang et al [7].…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…The consideration of the two ternary compounds reported by Clark-Ca2Mg6Zn3 and Ca2Mg5Zn13-resulted in the best consistency with the experimental results reported in the literature, e.g., [33]. Bakhsheshi-Rad et al [38] investigated the influence of Zn content on the microstructure, phase compositions and corrosion resistance of binary Mg-xZn and ternary Mg-0.8Ca-xZn (x = 1.25, 2.5, 4 wt %) alloys. The effect of the Ca content in Mg-4Zn-xCa (x = 0.18-2.2 wt %) on the microstructure, phase composition and morphology has been systematically studied by Zhang et al [7].…”
Section: Resultsmentioning
confidence: 69%
“…The literature shows contradicting information regarding the ternary compounds in the Mg-Zn-Ca system. The phase formation and microstructure evolution during solidification, solution treatment and ageing of an Mg-Ca-Zn alloy have been predicted qualitatively and quantitatively based on computational thermodynamics by many authors, e.g., [36][37][38][39]. Wasiur-Rahman and Medraj [39] performed the critical assessment of the experimental data accumulated to date in line with thermodynamic modeling of phase equilibria to determine the most likely description of this system and to eliminate the self-contradicting experimental observations.…”
Section: Resultsmentioning
confidence: 99%
“…Unfortunately, pure magnesium has low corrosion resistance and high degradation rate especially under exposure tohuman body fluid [3,4]. Moreover, mechanical properties of magnesium are also lower than the expected to be load bearing application [1].…”
Section: Introductionmentioning
confidence: 99%
“…To process Mg-Zn-Ca alloy, melting process was commonly used [4,7], but in this study, powder metallurgy process was used. Conventional powder metallurgy is one of a processing method which is known for its simplicity.…”
Section: Introductionmentioning
confidence: 99%
“…Yan et al [18] demonstrated that Mg-Zn alloy performed better than Ti3Al-2.5V by promoting healing and reducing inflammation. Based on the aforementioned considerations, several Mg alloys have been investigated with the addition of different contents of Ca and Zn [19][20][21][22]. All the previous studies acknowledge the biosafety of Ca and Zn addition in magnesium and support the great potential of Ca-and Zn-containing magnesium alloys for implant applications.…”
Section: Introductionmentioning
confidence: 99%